Analysis Of Arabic Learning In Mts N Binjai: Problematika And Solutions - Zulheddi Zulheddi; Azizah Hanum OK; Arief Dharmawan Siregar; M Fajri Syahroni Siregar (At-Tarbiyat, 2021)
This study aims to analyze more deeply the learning process of Arabic language in Madrasah Tsanawiyah Binjai State and problems that occur in the process of learning Arabic. This research is qualitative research in the form of descriptive and the results are described with words according to the category to get conclusions. Data collection. This research was conducted by method; (1) Observation; (2) Interviews; (3) Documentation. The subjects in this study were grade VII teachers, and the object in this study was a grade VII student at Madrasah Tsanawiyah Negeri Binjai. The results of this study show that; (1) The learning process of Arabic language in Madrasah Tsanawiyah Binjai still needs to be evaluated (2) Problems that arise in Arabic l anguage learning in Madrasah Negeri Tsanawiyah which is mostly due to the lack of understanding of students on the material. given by the teacher, the motivation of the students is low and some teachers have low competence in teaching Arabic andthecurriculum managementis alsostill poor. (3) The efforts made as a solution are to improve the competence of teachers, prepare appropriate teaching materials, and make teachers as motivators.